2000
DOI: 10.4102/jsava.v71i1.671
|View full text |Cite
|
Sign up to set email alerts
|

Babesia bovis and B. bigemina DNA detected in cattle and ticks from Zimbabwe by polymerase chain reaction

Abstract: From blood collected from 94 cattle at 12 locations in the eastern and northeastern areas of Zimbabwe, DNA was extracted and analysed by polymerase chain reaction with primers previously reported to be specific for <em>Babesia bigemina</em> and <em>Babesia bovis</em>. Overall, DNA of <em>Babesia bigemina</em> was detected in the blood of 33/94 (35 %) cattle and DNA from <em>B. bovis</em> was detected in 27/58 (47 %) of cattle. The prevalence of DNA of <em>B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 14 publications
1
25
1
3
Order By: Relevance
“…In the results from the present study, the calves also showed higher values (P < 0.01). The frequency of positive samples for B. bigemina was 34%, similar to what was found by Smeenk et al (2000), who observed in Zimbabwe that 35% of the animals were positive. These findings were higher than what was found by Brito et al (2007) in Rondônia, with a frequency of 3.09%, also using molecular diagnostic PCR.…”
Section: Discussionsupporting
confidence: 75%
“…In the results from the present study, the calves also showed higher values (P < 0.01). The frequency of positive samples for B. bigemina was 34%, similar to what was found by Smeenk et al (2000), who observed in Zimbabwe that 35% of the animals were positive. These findings were higher than what was found by Brito et al (2007) in Rondônia, with a frequency of 3.09%, also using molecular diagnostic PCR.…”
Section: Discussionsupporting
confidence: 75%
“…Preliminary investigations could attribute this to movement of livestock as interviews with the veterinary personnel indicated that farmers in Bikita district are purchasing heavy framed cattle from the eastern parts of the country, particularly in Chipinge, in order to genetically improve their breeds and fetch high prices at the cattle markets. Chipinge is the traditionally known focal area of R. microplus in Zimbabwe (Katsande et al, 1999b;Katsande et al, 1996;Mason and Norval, 1980;Smeenk et al, 2000), so this movement of cattle could have led to the movement of the tick in the area. The presence of R. microplus in an area is a threat to livestock production because of its invasive character, acaricide resistance and the fact that it transmits the most pathogenic form of bovine babesiosis .…”
Section: Discussionmentioning
confidence: 99%
“…The application of PCR-based tests to the study of the epidemiology of anaplamosis is still incipient, but characteristics of high sensitivity and specificity have been verified by several authors (Fahrimal et al 1992, Figueroa et al 1992, Smeenk et al 2000, Almeria et al 2001) for the detection of infection both in the vertebrate hosts and ticks.…”
Section: Introductionmentioning
confidence: 99%